A compact monopolar patch antenna with bandwidth‐enhancement under dual‐mode resonance. Issue 3 (11th December 2019) - Liu, Neng‐Wu; Sun, Mei‐Jiao; Zhu, Lei; Jia, Zhi‐Hui; Ji, Lu‐Yang; Fu, Guang; Zheng, Hui‐Li
Abstract: A compact monopolar microstrip patch antenna (MPA) with enhanced‐bandwidth is proposed. In order to achieve the miniaturized patch, the zeroth‐order mode of the MPA instead of its higher‐order modes is employed at first by loading the shorting pin around the center of the patch. After that, a L‐shaped microstrip line with a shorting pin is introduced at the periphery of the patch radiator to excite an additional non‐radiative mode for bandwidth enhancement. In final, the proposed MPA is fabricated and measured. The results illustrate that the antenna generates an enhanced‐bandwidth of about 4.1% ranging from 2.39 to 2.49 GHz, which is significantly larger than that of the traditional MPA around 1%. Meanwhile, the dimensions of the radiating patch are obviously decreased down due to the employment of zeroth‐order mode, which are kept as small as about 0.17 λ 0 × 0.22 λ 0 × 0.026 λ 0 ( λ 0 is the free‐space wavelength).